(untitled) (Annals of Medical Research, 2022)
Aim: In this study, we aimed to evaluate the effects of gender, age, time of admission to the emergency department, season, drug used, the time patients were admitted to the emergency department following the drugs administration, and psychiatric illness history on the clinical outcome of patients by examining the patients who admitted to our emergency department after taking suicidal drugs. Materials and Methods: The data of the study were obtained as a result of the retrospective examination of the cases who took drugs for suicidal purposes, who admitted to the emergency department of our hospital between January 2019-January 2020. We divided those who were discharged and admitted to the ward as good clinical outcome, and those who were admitted to the intensive care unit and those who died had poor clinical outcome. We statistically analyzed the effects of age, gender, the active substance used, the time of admission to the emergency department, the number of hours after which it was presented, a previous suicide attempt, and a history of psychiatric illness on clinical outcomes. Results: 295 patients were included in the study. 64.4% (190) of the cases were female and 35.6% (105) were male. The mean age of the patients is 32.9, and the majority of them are in the 25-34 age group (31.5%). The fact that the patients were male, admitted to the emergency room 4 hours after taking the drug, admitted to the emergency room between 00.00-07.59, committed suicide with psychiatric medication, had a previous suicide attempt and diagnosis of psychiatric illness, had a statistically poor clinical outcome(p<0.001). Conclusion: As a result, the history of the patients, the active substances they took, the hours and duration of their arrival to the emergency department can be used to predict the occurrence of serious clinical pictures in suicidal drug intake.